2013
DOI: 10.1007/s13277-013-0902-0
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA 181a improves proliferation and invasion, suppresses apoptosis of osteosarcoma cell

Abstract: MicroRNA 181a (miR-181a) was found dysregulated in a variety of human cancers and significantly associated with clinical outcome of cancer patients. However, the direct role of miR-181a has not yet been characterized in osteosarcoma progression. This study was aimed at investigating the effects of miR-181a on osteosarcoma cell biological behavior. First, the expression of miR-181a in osteosarcoma cell lines (MG63, HOS, SaOS-2, and U2OS) and a human osteoblastic cell line (hFOB1.19) was detected by qRT-PCR. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…In contrast, miR-181a is reported to promote G1/S transition and cell proliferation in pediatric acute myeloid leukemia by targeting ATM [18]. Jianwei and colleges demonstrated that miR-181a improves proliferation and invasion and suppresses apoptosis of osteosarcoma cells [19]. Data from the current study showed that miR-181a is increased in human keloid fibroblasts, although its functions and molecular mechanisms remain to be established.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, miR-181a is reported to promote G1/S transition and cell proliferation in pediatric acute myeloid leukemia by targeting ATM [18]. Jianwei and colleges demonstrated that miR-181a improves proliferation and invasion and suppresses apoptosis of osteosarcoma cells [19]. Data from the current study showed that miR-181a is increased in human keloid fibroblasts, although its functions and molecular mechanisms remain to be established.…”
Section: Discussionmentioning
confidence: 55%
“…Normal chondrocytes, chondrosarcoma, and osteosarcoma have been shown to express miRNA-181a [1,2,6,9]. The current study has made an important contribution in terms of how it demonstrates a pathogenic role for miR181a, particularly in terms of the upregulation of VEGF, and how it may respond to hypoxia in chondrosarcoma cells.…”
Section: Where Do We Need To Go?mentioning
confidence: 71%
“…Previous studies [1,2,6,9] demonstrated that miRNA-181a is neither cell nor tumor specific. Normal chondrocytes, chondrosarcoma, and osteosarcoma have been shown to express miRNA-181a [1,2,6,9].…”
Section: Where Do We Need To Go?mentioning
confidence: 98%
See 2 more Smart Citations